High-grade transformation of a polymorphous adenocarcinoma of the salivary gland: a case report and review of the literature - Miserocchi, Giacomo; Bassi, Massimo; De Luca, Giovanni; Calpona, Sebastiano; De Rosa, Francesco; Bongiovanni, Alberto; Parisi, Elisabetta; Di Menna, Giandomenico; De Vita, Alessandro; Liverani, Chiara; Spadazzi, Chiara; Cocchi, Claudia; et al. (Frontiers in Oncology, 2023)
Background: Polymorphous Adenocarcinoma (PAC) represents the second most widespread neoplasm of the minor salivary glands. These tumors rarely develop a histological progression from low-grade to high-grade malignancy, named “high-grade transformation” (HGT). Only 9 cases are described in literature. Case description: Here we describe the case of a 76-year-old male patient with a PAC recurrence of the oral floor displaying HGT and we explore the tumor cytomorphological features, genomic profiling, and the patient's clinical management. The tumor mass was characterized by poorly atypical cellular elements with vesicular nuclei and comedonecrosis foci. The growth pattern was predominantly solid, tubular and cribriform. The lesion did not show microsatellite instability, nor targeted molecular alterations. The case was successfully treated with radical surgery followed by radiotherapy. Conclusion: We report for the first time the recurrence of a PAC with HGT arises in the oral floor after 20 years from the primary lesion. These preliminary data and the literature analysis enhance the knowledge of this extremely rare disease.